In silico screening of Andrographis paniculata secondary metabolites as anti-diabetes mellitus through PDE9 inhibition - Netty Ino Ischak; La Aman Ode; Hamsidar Hasan; Akram La Kilo; Aiyi Asnawi (Wolters Kluwer Medknow Publications, 2023)
Background and purpose: Andrographis paniculata (AP) has long been used as an anti-diabetic agent, but the mechanism of action and active substance responsible for the anti-diabetic effect, particularly by inhibiting phosphodiesterase-9 (PDE9), which is one of the targets of anti-diabetic medications, have not been reported. The aim of the present study was to identify a new anti-diabetes candidate from secondary metabolite compounds of AP through PDE9 inhibition. Experimental approach: In order to prepare the chemical structures of the secondary metabolites of AP and PDE9, docking and molecular dynamics simulations were run using Discovery Studio Visualizer, AutoDockTools, AutoDock, and Gromacs, along with a few other supporting software packages. Findings/Results: Molecular docking simulations showed that two of the 46 secondary metabolites of AP had higher free energies of binding, C00003672 (-11.35 kcal/mol) and C00041378 (-9.27 kcal/mol), than native ligand (-9.23 kcal/mol). The results of molecular dynamics showed that compound C00041378 interacted with TRY484 and PHE516, two active side residues of PDE9. ΔGMMGBSA interactions of PDE9 with C00003672, C00041378, and 49E compounds are 51.69, -56.43, and -48.13 kcal/mol, respectively, as well as ΔGMMPBSA interactions of PDE9 with C00003672, C00041378, and 49E compounds, were -12.26, -16.24, and -11.79 kcal/mol kcal/mol, respectively. Conclusions and implications: Based on the evaluations of AP secondary metabolites using docking and molecular dynamics simulation, it is suggested that the C00041378 compound has the potential to be an antidiabetic candidate by inhibiting PDE9.